Proceedings of the 2021 Conference on Empirical Methods in Natural Language Processing 2021
DOI: 10.18653/v1/2021.emnlp-main.572
|View full text |Cite
|
Sign up to set email alerts
|

CrossFit: A Few-shot Learning Challenge for Cross-task Generalization in NLP

Abstract: Humans can learn a new language task efficiently with only few examples, by leveraging their knowledge obtained when learning prior tasks. In this paper, we explore whether and how such cross-task generalization ability can be acquired, and further applied to build better few-shot learners across diverse NLP tasks. We introduce CROSSFIT , a problem setup for studying cross-task generalization ability, which standardizes seen/unseen task partitions, data access during different learning stages, and the evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 118 publications
0
66
0
Order By: Relevance
“…In our paper, we efficiently achieve few-shot task adaptation by inferring the task-skill allocation matrix for new tasks and fine-tuning skill parameters, which were previously learned via multitask learning. In fact, Ye et al (2021) found that this pre-training routine is superior to meta-learning in CrossFit. A similar attempt to recompose modular knowledge learnt on previous tasks has been recently explored by Ostapenko et al (2021).…”
Section: Related Workmentioning
confidence: 98%
See 4 more Smart Citations
“…In our paper, we efficiently achieve few-shot task adaptation by inferring the task-skill allocation matrix for new tasks and fine-tuning skill parameters, which were previously learned via multitask learning. In fact, Ye et al (2021) found that this pre-training routine is superior to meta-learning in CrossFit. A similar attempt to recompose modular knowledge learnt on previous tasks has been recently explored by Ostapenko et al (2021).…”
Section: Related Workmentioning
confidence: 98%
“…In addition, in the wake of the recent surge of interest in massively multitask few-shot NLP models (Min et al, 2021;Wei et al, 2021;Aribandi et al, 2021;Sanh et al, 2022;Karimi Mahabadi et al, 2021, inter alia), we also evaluate our latent-skill model on CrossFit (Ye et al, 2021). This benchmark recasts 160 NLP tasks (including QA, conditional text generation, classification, and other types such as regression) as textto-text generation problems.…”
Section: Fine-grained Skill Selectionmentioning
confidence: 99%
See 3 more Smart Citations